The Routledge companion to marketing research - Moutinho, Luiz; Wright, Len Tiu; Stone, Merlin 1948-; Bagozzi, Richard P. (Milton Park, Abingdon, Oxon Routledge, 2021)
"This single volume reference provides an alternative to traditional marketing research methods handbooks, focusing entirely on the new and innovative methods and technologies that are transforming marketing research and practice. Including original contributions and case studies from leading global specialists, this handbook covers many pioneering methods such as: Methods for the analysis of user- and customer-generated data, including opinion mining and sentiment analysis. Big data. Neuroscientific techniques and physiological measures. Voice prints. Human-computer interaction. Emerging approaches such as shadowing, netnographies and ethnographies Transcending the old divisions between qualitative and quantitative research methods, this book is an essential tool for market researchers in academia and practice"--
PART I: Conceptual
1. The evolution of marketing research / Merlin Stone, Len Tiu Wright and Luiz Moutinho
2. Combining big data and marketing research to create customer insight / Len Tiu Wright, Merlin Stone, Robin Robin and Eleni Aravopoulou
3. Interactive marketing, customer information and marketing research / Merlin Stone, Eleni Aravopoulou, Neil Woodcock, Paul Laughlin and Ryan Stott
4. Business models and marketing research / Brett Parnell, Ryan Stott, Merlin Stone and Eleni Aravopoulou

PART II: Methods
5. Mixed-methods research: why and how to use it / Pantea Foroudi, Maria Palazzo and Merlin Stone
6. Case studies as a research methodology / Abraham Joseph and Suraksha Gupta
7. Establishing validity and reliability in case study research projects / Samina Sumrin and Suraksha Gupta
8. Encouraging information disclosure on social media platforms in consumer marketing research / Robin Robin, Hazem Gaber and Len Tiu Wright
9. Artificial intelligence in marketing and marketing research / Merlin Stone, Luiz Moutinho, Yuksel Ekinci, Ashraf Labib, Geraint Evans, Eleni Aravopoulou, Paul Laughlin, Matt Hobbs, Jon Machtynger and Liz Machtynger
10. Data management and marketing research / Merlin Stone, Tony Mooney and Paul Laughlin
11. Deciding on and using research data / Merlin Stone, Len Tiu Wright, Robin Birn and Luiz Moutinho
12. The Archive of Market and Social Research: looking backwards to look forwards / Robin Birn, Merlin Stone, Nektarios Tzempelikos, Kaouther Kooli and Emmanuel Kosack
13. Key issues in managing marketing research and customer insight / Robin Birn and Merlin Stone

PART III: Techniques
14. Brain’s valuation networks and consumers’ neuroscience methods in the fuzzy front-end innovation process / Jyrki Suomala and Pekka Berg
15. An introduction to the use of EEG in marketing research / Reem Refai A. Mahmoud and Richard P. Bagozzi
16. How brand interest mediates the relationship between cross-media investments and word-of-mouth and purchase intention: a mixture-amount moderated mediation model / Patrick De Pelsmacker, Nathalie Dens, Peter Goos and Leonids Aleksandrovs
17. The effect of voice emotion response on brand recall by gender / Wan-Chen Wang, Maria Helena Pestana and Luiz Moutinho
18. Identifying the drivers of shopper attention, engagement, and purchase / Raymond R. Burke and Alex Leykin

PART IV: Applications
19. Researching older citizens and their attitudes towards smart homes / Merlin Stone, Eleni Aravopoulou and Geraint Evans
20. Marketing research and customer loyalty in an Islamic banking culture in the Middle East: a case study of Jordan / Ala’ Omar Dandis and Len Tiu Wright
21. Smart cities and smart transport – the role of data and insight / Merlin Stone, Eleni Aravopoulou, Jonathan Knapper and Geraint Evans
22. Design, innovation and marketing research / James Woudhuysen, Emmanuel Kosack and Merlin Stone
23. Researching the advantage of low quality in short life cycle products / Yang Sun, Helen Huifen Cai, Rui Su, Qianhui Shen and Merlin Stone

PART V: Reflections and futures
24. Foresight in marketing and marketing research / Sérgio Brodsky
25. Fakes and futures / Merlin Stone, Eleni Aravopoulou, Geraint Evans, Esra AlDhaen and Brett Parnell
26. Futuring marketing research – strategy / Luiz Moutinho
27. Further futuring in marketing research – techniques / Luiz Moutinho
28. A practitioner’s view of customer insight – past, present and future / Tony Mooney
29. A practitioner’s view of customer insight – past, present and future / Paul Laughlin
30. Epilogue a more strategic look at the future of marketing research / Merlin Stone, Len Tiu Wright and Luiz Moutinho
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Marketing research